Let's analyze each equation one by one to determine the number of solutions:
-
Equation: \( x - 7 = 7 - x \)
Solving:
- Rearranging gives: \( x + x = 7 + 7 \)
- This simplifies to: \( 2x = 14 \)
- Thus, \( x = 7 \)
Number of solutions: 1 solution
-
Equation: \( 3(x + 5) = 3x + 5 \)
Solving:
- Expanding the left side gives: \( 3x + 15 = 3x + 5 \)
- Subtracting \( 3x \) from both sides results in: \( 15 = 5 \)
- This statement is false.
Number of solutions: 0 solutions
-
Equation: \( 10 - x = 25 \)
Solving:
- Rearranging gives: \( -x = 25 - 10 \)
- Which simplifies to: \( -x = 15 \)
- Thus, \( x = -15 \)
Number of solutions: 1 solution
-
Equation: \( 2(x + 4) = 2x + 5 + 3 \)
Solving:
- Expanding the left side gives: \( 2x + 8 = 2x + 8 \)
- This results in a true statement (both sides are equal).
Number of solutions: Infinite solutions (the equation is true for all values of \( x \))
Summary of Number of Solutions:
- \( x - 7 = 7 - x \) → 1 solution
- \( 3(x + 5) = 3x + 5 \) → 0 solutions
- \( 10 - x = 25 \) → 1 solution
- \( 2(x + 4) = 2x + 5 + 3 \) → Infinite solutions